The influence of willingness to change and perceived technology opportunities on corporate entrepreneurship and labor growth in non-financial companies in Central Java - Dewi, Septiana Novita; Haryanto, Aris Tri; Nugroho, Anggoro Panji (2025)
This study is categorized as a cross-sectional study, meaning that it only takes research data from a certain period. The unit of analysis is the organization because each respondent's answer represents their organization, which in this study is a non-financial company in Central Java. The sample used was 120 respondents, with a purposive sampling technique that took the criteria of non-financial companies that had been established for at least 3 years. The analysis used was path analysis. The results of the study showed that the willingness to change had a positive and significant effect on corporate entrepreneurship. Perceived technological opportunities had a positive and significant effect on corporate entrepreneurship. The willingness to change had a positive and significant effect on workforce growth. Technological opportunities had a negative and not significant effect on workforce growth. Corporate entrepreneurship had a positive and significant effect on workforce growth. The results of the regression coefficient test showed that 74.7% of workforce growth in Non-Financial Companies in Central Java was explained by the willingness to change, perceived technological opportunities and corporate entrepreneurship. The results of the path analysis showed that the willingness to change was more effective through indirect channels. Perceived technological opportunities were more effective through indirect channels. The most dominant influence in influencing workforce growth was the increase in the willingness to change mediated by corporate entrepreneurship.